Dual‐Ion Batteries: Bubble‐Sheet‐Like Interface Design with an Ultrastable Solid Electrolyte Layer for High‐Performance Dual‐Ion Batteries (Adv. Mater. 17/2017). Issue 17 (May 2017) - Qin, Panpan; Wang, Meng; Li, Na; Zhu, Haili; Ding, Xuan; Tang, Yongbing
Abstract : In article number1606805, Yongbing Tang and co‐workers report a bubble‐sheet‐like aluminum foil used as anode and current collector in a dual‐ion battery. This novel structure helps guide the Al‐Li alloying position and confines the volumetric change, and thus results in excellent long‐term cycling stability, featuring 99% capacity retention within 1500 cycles at 2 C.